Short-term outcomes of robotic vs. laparoscopic surgery for rectal cancer after neoadjuvant therapy: a meta-analysis - Zhang, Yuqiang; Dong, Bo; Li, Guanglin; Ye, Wei (Frontiers in Surgery, 2024)
Background: The effect of robotic surgery (RS) for rectal cancer after neoadjuvant therapy is still controversial, and a comprehensive search and analysis of the current relevant evidence is necessary. Our study aimed to evaluate the efficacy of RS for rectal cancer after neoadjuvant therapy compared with conventional laparoscopic surgery (LS). Methods: Up to August 23, 2023, Embase, PubMed, Web of Science, and Cochrane databases were searched for studies of RS for rectal cancer after neoadjuvant therapy. Odds ratio (OR) or mean difference (MD) was used to calculate the effect sizes using RevMan 5.3. Results: A total of 12 studies reporting on 11686 participants were included. Compared with LS, RS increased the operative time (MD 35.16 min; 95% CI: 16.24, 54.07), but it did significantly reduce the risk of the conversion to open surgery (OR 0.46, 95% CI 0.40, 0.53) and improved the TME incomplete rate (OR 0.40, 95% CI 0.17, 0.93). Moreover, there were no difference in total postoperative complications (OR 1.13, 95% CI 0.84, 1.52), circumferential resection margin positivity (OR 0.90, 95% CI 0.63, 1.27), distal margin positive (OR 0.60, 95% CI 0.29, 1.22), blood loss (MD -11.57 ml; 95% CI: -39.09, 15.94), length of hospital stay (MD -0.08 days; 95% CI: -1.26, 1.10), mortality (OR 0.59, 95% CI 0.29, 1.21), lymph node harvested (MD 0.69.; 95% CI: -0.43, 1.82), and the time of first flatus (MD -0.47 days; 95% CI: -1.19, 0.25) between the two groups. Conclusions: RS was associated with superiority over LS in reducing the risk of the conversion to open surgery and improving TME incomplete rate, which suggested that RS could be an effective method for treating rectal cancer after neoadjuvant therapy.